The effect of gadodiamide on cancer cell lines - Fujimoto, T.; Finnegan, M. (Experimental Oncology, 2009)
Aim: Recent literature suggests that some human cancer cell lines possess a calcium cation receptor. Human myeloma cell lines have demonstrated stimulated cell proliferation by the gadolinium cation through this receptor, and osteosarcoma cell lines possess the same cation receptor. Although enhanced MRI is a very useful diagnostic tool for the treatment of sarcoma in the orthopedic area, incorporating the use of MRI contrast agents based on gadolinium raises the possibility of the stimulation of cancer cell growth. Methods: Human myeloma (RPMI 8226), osteosarcoma (Saos-2) and rat osteosarcoma (UMR-106) cell lines were exposed to various concentrations of common MRI contrast agent gadodiamide (Omniscan®) (5 μM, 50 μM, 500 μM, 5 mM, 50 mM) in a culture medium. The response of the cells was then assessed by measuring cell proliferation and DNA synthesis. Results: Treatment with 5 μM to 5 mM gadodiamide did not stimulate cell proliferation; only cells exposed to 50 mM gadodiamide showed suppressed proliferation rates. Conclusions: Since intravenously injected gadodiamide is diluted from 500 μM to 1 mM by patient blood flow at enhanced MRI examinations, the results of the present study suggest that gadodiamide has not effect on these types of cancer cells.